2012
DOI: 10.1155/2012/862879
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cisplatin-Induced Apoptosis and of Cisplatin Sensitivity: Potential of BIN1 to Act as a Potent Predictor of Cisplatin Sensitivity in Gastric Cancer Treatment

Abstract: Cisplatin is the most important and efficacious chemotherapeutic agent for the treatment of advanced gastric cancer. Cisplatin forms inter- and intrastrand crosslinked DNA adducts and its cytotoxicity is mediated by propagation of DNA damage recognition signals to downstream pathways involving ATR, p53, p73, and mitogen-activated protein kinases, ultimately resulting in apoptosis. Cisplatin resistance arises through a multifactorial mechanism involving reduced drug uptake, increased drug inactivation, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 34 publications
1
72
0
3
Order By: Relevance
“…Previous reports showed that Cisplatin stimulated apoptosis via intrinsic and extrinsic pathways [31] and cFLIP knockdown increased sensitivity to Cisplatin [17]. CoCl 2 is a chemical inducer of hypoxia-inducible factor-1 (HIF1) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that Cisplatin stimulated apoptosis via intrinsic and extrinsic pathways [31] and cFLIP knockdown increased sensitivity to Cisplatin [17]. CoCl 2 is a chemical inducer of hypoxia-inducible factor-1 (HIF1) [32].…”
Section: Discussionmentioning
confidence: 99%
“…This p53 gene stimulates expression of Bcl-2 family including Bax, and can bind to one or more anti-apoptotic proteins in mitochondria, such as Bcl-XL (Chipuk, et al, 2003;Marsden, et al, 2002). On the other hand, cisplatin also plays a role in mediating the activation of the p53 protein, which is followed by the occurrence of DNA damage (Tanida, et al, 2012), so the mutation of p53 gene on T47D cells can inhibit cisplatin to induce apoptosis. However, previous studies had proved that the mechanism of cisplatin to induce apoptosis was by causing downregulation of Bcl-2 gene on MCF 7 cell lines (Thomadaki and Scorilas 2007) and T47D cell lines (Mokhtari, et al, 2012).…”
Section: (D) (E)mentioning
confidence: 99%
“…Also, Amphiphysin 2 supports T-cell mediated immune surveillance against tumors. The mechanism by which Amphiphysin 2 promotes tumor suppression is unknown, though it has been shown to promote apoptosis in cancer cells via activation of Bax 90 and is known to promote DNA repair by binding and inhibiting poly (ADP-ribose) polymerase (PARP1), a key component in base excision repair pathway via its BAR domain. 89 …”
Section: Cell Cycle Regulationmentioning
confidence: 99%